(untitled) (Research, Society and Development, 2022)
The Amazon has vast biodiversity, such as seeds, fruits, fish, and oilseeds. This aspect encourages a growing interest in several segments to find new products and sources of nutrients with functional properties. In addition to the functional properties, there is the presence of probiotic microorganisms that have protective and regulatory properties of the intestinal microbiota. In this way, it is essential to search for new products with probiotic potential since it is of paramount importance to maintain the balance of the intestinal microbiota due to its influence on the host’s health. Therefore, the objective of this study was to carry out bibliographic research with a qualitative approach, through a literature review, in the databases Digital Library of Theses and Dissertations, Portal de Periódicos Capes, and Google Scholar in the last 15 years (2007-2021). The unilateral term probiotic defined the search strategy in combination with relative terms. The research sought fifteen publications about Amazonian natural resources as probiotic sources based on the analyzed studies. Among the works cited, it is observed that there is a trend of investigations about the food benefits and a search for new products using raw materials from the Amazon and other regions of Brazil, through research, predominantly empirical, that evaluate from parameters physical-chemical, sensorial, and molecular, the results obtained. However, further studies are still needed on new formulations with probiotic characteristics.